Ubiquitin B in cervical cancer: critical for the maintenance of cancer stem-like cell characters. - Yuan Tian; Wencheng Ding; Yingying Wang; Teng Ji; Shujuan Sun; Qingqing Mo; Pingbo Chen; Yong Fang; Jia Liu; Beibei Wang; Jianfeng Zhou; Ding Ma; et al. (PLoS ONE, 2013)
Cervical cancer cells exhibit an increased requirement for ubiquitin-dependent protein degradation associated with an elevated metabolic turnover rate. Ubiquitin, which is a small, highly conserved protein expressed in all eukaryotic cells, can be covalently linked to certain target proteins to mark them for degradation by the ubiquitin-proteasome system. Previous studies highlight the essential role of Ubiquitin B (UbB) and UbB-dependent proteasomal protein degradation in histone deacetylase inhibitor (HDACi) -induced tumor selectivity. We hypothesized that UbB plays a critical role in the function of cervical cancer stem cells. We measured endogenous UbB levels in mammospheres in vitro by real-time PCR and Western blotting. The function of UbB in cancer stem-like cells was assessed after knockdown of UbB expression in prolonged Trichostatin A-selected HeLa cells (HeLa/TSA) by measuring in vitro cell proliferation, cell apoptosis, invasion, and chemotherapy resistance as well as by measuring in vivo growth in an orthotopic model of cervical cancer. We also assessed the cancer stem cell frequency, tumorsphere formation, and in vivo growth of human cervical cancer xenografts after UbB silencing. We found that HeLa/TSA were resistant to chemotherapy, highly expressed the UbB gene and the stem cell markers Sox2, Oct4 and Nanog. These cells also displayed induced differentiation abilities, including enhanced migration/invasion/malignancy capabilities in vitro and in vivo. Furthermore, an elevated expression of UbB was shown in the tumor samples of chemotherapy patients. Silencing of UbB inhibited tumorsphere formation, lowered the expression of stem cell markers and decreased cervical xenograft growth. Our results demonstrate that UbB was significantly increased in prolonged Trichostatin A-selected HeLa cells and it played a key role in the maintenance of cervical cancer stem-like cells.